2017
DOI: 10.3390/recycling2040018
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Moderating Role of Perceived Lack of Facilitating Conditions on Household Recycling Intention in Kano, Nigeria

Abstract: Improper handling of household solid waste causes problems that affect public health and the environment, as well as the aesthetic nature of cities. This paper aims to determine if the theory of planned behavior (TPB), and its extended version can be used to predict household recycling intention (RI), and whether perceived lack of facilitating conditions have a moderating role on households' RI in Nigeria. Data from a sample of 393 households from Kano metropolis Nigeria were analyzed using structural equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 64 publications
6
35
0
Order By: Relevance
“…Apart from recycling intentions, past recycling behaviours should also be studied to observe possible gaps between intentions and behaviours. A number of studies also added constructs such as 'personal norm', 'awareness of consequences', 'environmental knowledge', 'past behaviour', 'self-identity', and 'situation factors' to the extended TPB frameworks to explain individuals recycling intentions, which appeared to be relevant [54,55,57,[83][84][85]. Therefore, future studies could use such extended TPB models to predict young citizens' recycling intentions and behaviours in India.…”
Section: Limitations and Future Research Needsmentioning
confidence: 99%
“…Apart from recycling intentions, past recycling behaviours should also be studied to observe possible gaps between intentions and behaviours. A number of studies also added constructs such as 'personal norm', 'awareness of consequences', 'environmental knowledge', 'past behaviour', 'self-identity', and 'situation factors' to the extended TPB frameworks to explain individuals recycling intentions, which appeared to be relevant [54,55,57,[83][84][85]. Therefore, future studies could use such extended TPB models to predict young citizens' recycling intentions and behaviours in India.…”
Section: Limitations and Future Research Needsmentioning
confidence: 99%
“…The previous research was conducted at the University of South Florida [16] and the University of Twente [17] suggests that knowledge does not correlate with intention. Prior study found that attitudes associated with intention (r = 0.213, p <.000) [18]. Also, Gadiraju suggested that attitude was related to intention (r = 0.310, p <0.01).…”
Section: Introductionmentioning
confidence: 89%
“…Research that accounts for attitude toward recycling, recycling-related subjective norm, and perceived recycling control can help explain why individuals recycle [19]. Other scholars have explained recycling behavior in terms of implementation intention.…”
Section: Recycling As Planned Behaviormentioning
confidence: 99%
“…Studying behavioral control is important in the context of recycling because perceived behavioral control can be an important determinant of behavioral intention [20,21], and individuals are less likely to act on their intentions when infrastructure is lacking or they are unsure how to use it [1,19,22]. It follows that individuals will have stronger intentions to recycle and be more likely to actually recycle if they have good understanding of how and where to recycle.…”
Section: Recycling As Planned Behaviormentioning
confidence: 99%
See 1 more Smart Citation